2003
DOI: 10.1073/pnas.2233745100
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the bypassing ribosome travels through the coding gap

Abstract: In translational bypassing, a peptidyl-tRNA::ribosome complex skips over a number of nucleotides in a messenger sequence and resumes protein chain elongation after a ''landing site'' downstream of the bypassed region. The present experiments demonstrate that the complex ''scans'' processively through the bypassed region. This conclusion rests on three observations. (i) When two potential ''landing sites'' are present, the protein sequence of the product shows that virtually all ribosomes land at the first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…2E). Our proposal is reminiscent of the recent demonstration that the 50-nt bypassed region of the T4 gene 60 mRNA is also unfolded (Gallant et al 2003).…”
Section: Tmrna Unfoldingmentioning
confidence: 66%
“…2E). Our proposal is reminiscent of the recent demonstration that the 50-nt bypassed region of the T4 gene 60 mRNA is also unfolded (Gallant et al 2003).…”
Section: Tmrna Unfoldingmentioning
confidence: 66%
“…By analogy with bacterial (4), yeast (23), insect (10), and viral (81) systems, we had originally hypothesized that reliance on a restricted set of nonpreferred codons for the synthesis of capsid region polypeptides might cause a local depletion of the pools of minor tRNAs, thus retarding translocation of the ribosome along the viral mRNA. Ribosomal pausing at nonpreferred codons might impair poliovirus protein synthesis and processing in various ways, such as by amino acid misincorporation (55), by increasing the costs of translational proofreading (9), by frameshifting (18), by premature polypeptide chain termination (55), by degradation of the RNA template (23), and by disruption of the proteolytic processing of the polyprotein (56). On the other hand, it has been suggested that the nonrandom locations of nonpreferred codons between structural elements may facilitate proper folding of the nascent capsid proteins of poliovirus (19) and hepatitis A virus (66).…”
Section: Discussionmentioning
confidence: 99%
“…Knowing this potential, it is perhaps not surprising that Shine-Dalgarno sequences can also influence landing site selection by bypassing ribosomes because they linearly scan mRNA in the absence of special mRNA signals (4). Nevertheless, it is new, and its implications merit consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Long range translational bypassing in response to A-site codons whose aminoacyl-tRNAs are limiting has been demonstrated (2)(3)(4). In these cases, the peptidyl-tRNA dissociates from the ribosomal P-site codon, scans the coding gap, and re-pairs to mRNA at complementary triplets.…”
mentioning
confidence: 99%